2016
DOI: 10.1111/jsbm.12222
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity-Based Strategic Orientation, Knowledge Acquisition, and Entrepreneurial Alertness: The Perspective of the Global Sourcing Suppliers in China

Abstract: Taking the perspective of global sourcing suppliers in China, this paper investigates how the supplier firms acquire market and technical knowledge from the outsourcing partnerships differently based on their strategic orientations regarding the exploitation of opportunities versus resources. We find that suppliers whose strategy formulation is driven by the aggressive pursuit of valuable opportunities tend to be able to learn more from the outsourcing partners. Our results also show that market and technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 118 publications
1
28
0
Order By: Relevance
“…Additionally, McCaffrey (2014) suggested that knowledge might generate alertness. Therefore, entrepreneurs' knowledge (PK) positively influences EA in the opportunity identification process (Ma & Huang, 2016), which facilitate the adoption of eco‐innovation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Additionally, McCaffrey (2014) suggested that knowledge might generate alertness. Therefore, entrepreneurs' knowledge (PK) positively influences EA in the opportunity identification process (Ma & Huang, 2016), which facilitate the adoption of eco‐innovation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For example, Ardichvili and Cardozo (2003) [21] emphasize the significance of personality traits, social networks, and prior knowledge in predicting entrepreneurial alertness. Some scholars also recognize the importance of self-efficacy, entrepreneurial passion, technical ability, and market knowledge acquisition in determining an entrepreneur's alertness schema [22,23]. Others provide additional explanation by arguing the importance of a firm's path dependence [24] and external environmental complexity [25].…”
Section: Network Diversity Opportunity Identification and Venture Growthmentioning
confidence: 99%
“…Self-efficacy, social networks, and prior knowledge are the antecedents of entrepreneurial alertness in tourism SMEs. (Ma & Huang, 2016) Strategic orientation, knowledge acquisition and entrepreneurial alertness of global supplier firms.…”
Section: Citationmentioning
confidence: 99%